ChemInform Abstract: Stimuli‐Triggered Sol—Gel Transitions of Polypeptides Derived from α‐Amino Acid N‐Carboxyanhydride (NCA) Polymerizations. Issue 16 (March 2016) - He, Xun; Fan, Jingwei; Wooley, Karen L.
Abstract: Review: [60 refs.